2014
DOI: 10.14233/ajchem.2014.16930
|View full text |Cite
|
Sign up to set email alerts
|

Modification of MTT Assay for Precision and Repeatability and Its Mechanistic Implication

Abstract: The discovery of antibiotics is one of the key achievements of modern medicine. Antibiotic use has contributed enormously to human health. However, microorganisms can evolve and adjust to changes in their environment and have subsequently developed several protective mechanisms to reduce their susceptibility to antibiotics 1. More and more potent antibiotics lose their efficacy over time, rendering them useless for conditions they could once successfully treat 2-4. Therefore, there is an urgent need for screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Although Mosmann (1983) originally used acid isopropyl alcohol for extraction, Carmichael et al (1987) found that this solvent resulted in low optical absorption values and suggested the use of DMSO or mineral oil as alternatives. In strongly acidic media, the presence of the cationic MTT formazan results in a complete disappearance of the absorption at 575 nm (Wang et al, 2014). The acidic pH used in solubilization solvents has two effects: it modifies the absorption spectrum of the cationic formazan and also changes the absorption of any pH indicator if present.…”
Section: Viability Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Mosmann (1983) originally used acid isopropyl alcohol for extraction, Carmichael et al (1987) found that this solvent resulted in low optical absorption values and suggested the use of DMSO or mineral oil as alternatives. In strongly acidic media, the presence of the cationic MTT formazan results in a complete disappearance of the absorption at 575 nm (Wang et al, 2014). The acidic pH used in solubilization solvents has two effects: it modifies the absorption spectrum of the cationic formazan and also changes the absorption of any pH indicator if present.…”
Section: Viability Assaysmentioning
confidence: 99%
“…In addition to its use on mammalian cell cultures, the colorimetric MTT assay is employed for testing the viability of protozoan (Dias et al, 1999) and sperm cells of several species (Aziz, 2006;Van der Berg, 2015). Microbiological viability assay applications of tetrazolium salts are also well known and widely used (Thom et al, 1993;Bhupathirajua et al, 1999;Wang et al, 2014;Villegas-Mendoza et al, 2015;Grela et al, 2015), mainly for biofilms (Pérez et al, 2010;Trafny et al, 2013). MTT, CTC, XTT, and INT are the most widely used tetrazolium salts for assessment of microbial viability.…”
Section: Viability Assaysmentioning
confidence: 99%